Phosphorylation of the WWOX Protein Regulates Its Interaction with p73. (9th April 2020) - Lahav, Noa; Rotem‐Bamberger, Shahar; Fahoum, Jamal; Dodson, Emma‐Joy; Kraus, Yahel; Mousa, Reem; Metanis, Norman; Friedler, Assaf; Schueler‐Furman, Ora
Abstract: We describe a molecular characterization of the interaction between the cancer‐related proteins WWOX and p73. This interaction is mediated by the first of two WW domains (WW1) of WWOX and a PPXY‐motif‐containing region in p73. While phosphorylation of Tyr33 of WWOX and association with p73 are known to affect apoptotic activity, the quantitative effect of phosphorylation on this specific interaction is determined here for the first time. Using ITC and fluorescence anisotropy, we measured the binding affinity between WWOX domains and a p73 derived peptide, and showed that this interaction is regulated by Tyr phosphorylation of WW1. Chemical synthesis of the phosphorylated domains of WWOX revealed that the binding affinity of WWOX to p73 is decreased when WWOX is phosphorylated. This result suggests a fine‐tuning of binding affinity in a differential, ligand‐specific manner: the decrease in binding affinity of WWOX to p73 can free both partners to form new interactions. Abstract : Less is more : A single phosphorylation in the WWOX WW1 domain is sufficient to inhibit its binding to p73 peptide in vitro. Phosphorylation of WWOX WW1‐WW2 decreases its affinity to p73 peptide in vitro. In the context of the full WWOX and p73 proteins, this affinity decrease can serve as a platform for competition by other ligands with higher binding affinities to either WWOX or p73.